Analisa Kualitas Website Ahead Menggunakan Metode Webqual - Mohamad Rifandi Akbar; Eva Zuraidah (STMIK Budi Darma, 2023)
The Ahead website as a means of employee information used at PT. Adhimix Precast Indonesia, currently the use of the website has not been optimally carried out by employees, the constraints that are often experienced by employees are having difficulty logging in to access the website, there is no absence data, working hours, and the number of employee leaves that have not been integrated with the Ahead website so there is no need to open another website to do attendance. For this reason, researchers conducted an analysis of employee satisfaction as users of the Ahead website service on website quality using the webqual 4.0 method which focuses on 3 dimensions of webqual 4.0 namely Usability, Information Quality and Interaction Service Quality. to measure user satisfaction (User Satisfaction). This study used a statement instrument based on the webqual 4.0 dimension, using a questionnaire distributed to 71 respondents who were taken based on a random sampling sample from a population of 245 active employees. Data processing uses SPSS version 29. The results of the F test state that there is a joint influence of the 3 dimensions of Usability, Information Quality, Interaction Service Quality on user satisfaction, with a P-Value or significance of <0.001, meaning that the Probability value is <0 ,05. The results of the t test show that the Usability variable has no significant effect on user satisfaction, with a T_(Count ) value of 1.445 (T_Table value < 1.996), the influential variable is the quality of information. the interaction of the value of T_(Calculate) is 4.685. The results of the coefficient of determination test showed the effect of the 3 dimensions of webqual 4.0 on user satisfaction by 89.10%